Ultrasound fetal biometry in third trimester in urban Nepalese population - Kayastha, Bhuwan; Giri, Shahjan Raj; Gurung, Bibek; Panta, Om Biju (Nepal Mediciti Medical Journal, 2021)
INTRODUCTION: Fetal biometry is an important component of fetal growth surveillance and can detect small for gestation age fetuses. However, we use growth curves from studies done in other high-income countries and do not have a standard of our own. This study aims to study the deviation of biometry and expected fetal weight from these curves in pregnancy with normal birth weight term deliveries. METHODS: The study was a retrospective hospital record-based study including term delivery from 2018 May to 2020 January. All lowrisk patients visiting ultrasound OPD in our hospital in 3rd trimester were retrieved and included in the study. Patient with low AFI, major fetal anomaly, abnormal fetal heart rate, preterm delivery, birth weight less than 2500 gm (low birth weight), intrauterine fetal demise, preeclampsia or other complications were excluded from the study. Fetal biometry and expected fetal weight were evaluated. Data was entered in predesigned performa and analysis was performed with IBM SPSS 20.0. RESULTS: A total of 590 ultrasound examinations done in 372 patients were included in the study. Mean age of the patients was 30.78+/-3.98 years, median age was 30 years (IQ range-5). Approximately 316(53.6%) patients were under 30 years of age, 198(33.6%) patients were between 30-35 and 76(12.9%) patients were above 35 years. Median gestational age at birth was 39 weeks and median birth weight was 3120 grams. Median and percentile for various biometry was calculated. EFW was below 50th percentile in 424(71.9%) according to WHO chart. The median percentile for EFW was 30.6 (IQ-33.6). CONCLUSION: Expected fetal weight in Nepalese population is smaller than that predicted by WHO chart. Development of country specific fetal growth curve is recommended for accurate fetal growth surveillance.